Bifidobacteria from the gastrointestinal tract of animals: differences and similarities - Bunesova, V; Vlková, Eva; Rada, V; Killer, J; Musilova, S (Beneficial microbes, 2014)
At present, the genus Bifidobacterium includes 48 species and subspecies, and this number is expected to increase. Bifidobacteria are found in different ecological niches. However, most were originally isolated from animals, mainly mammals, especially during the milk feeding period of life. Their presence in high numbers is associated with good health of the host. Moreover, bifidobacteria are often found in poultry and insects that exhibit a social mode of life (honeybees and bumblebees). This review is designed as a summary of currently known species of the genus Bifidobacterium, especially focused on their difference and similarities. The primary focus is on their occurrence in the digestive tract of animals, as well as the specificities of animal strains, with regard to their potential use as probiotics.
Keywords: Animals; drůbež; Poultry; lidé; Bifidobacterium; gastrointestinální trakt; hmyz; Humans; Insecta; Gastrointestinal Tract; zvířata